Bread with stoned table olives – the union of two traditional products of excellence of Trás-os-Montes region, Portugal: preliminary results - Pawlak, Chalissa (2018)
The aim of the present work was to conduct a preliminary study on characterization of wheat bread with ”alcaparras”, produce that join two traditional products of excellence of Trás-os-Montes region, Northeast of Portugal. “Alcaparras” are processed from healthy green or yellow-green olives, which are broken using a wooden hammer separating the pulp of the core. The pulp is sliced into two approximately equal parts perpendicularly to the major axis of the fruit and placed on water, which is changed three to four times during a week. This treatment has the purpose of removing olive bitterness. Afterwards the product is stored in brine until consumption. Wheat breads were prepared with different percentages of “alcaparras”: 0, 3, 5 and 7% and stored at 25 °C for 4 days, being analysed every two days, regarding colour, dimensions, weight, pH, ash, fat and salt contents, as well as mesophiles, moulds and yeasts. The physic-chemical determinations were only made at 0 and 2 days because after the 4th day the bread had developed moulds. The breads presented pH values between 5.85-5.96, salt 0.51-1.01% (d.w.), ash 2.13-2.77% (d.w.) and fat 2.00-3.78% (d.w.) contents. The breads with the highest “alcaparras” percentage presented the lowest pH value and the highest salt and ash contents. As expected the breads with the lowest fat content were those without “alcaparras”. The mesophiles, moulds and yeasts varied between 1.3-7.4 log UFC/g (f.w.) and <1 to 5 log UFC/g (f.w.), respectively, being the highest values obtained at the end of storage. In conclusion bread with “alcaparras” is a promising product to be sold in gourmet shops; however, more studies are needed to increase its shelf-life.